Evaluation of Changes to the Education Curriculum in Indonesia as an Effort to Improve and Increase the Quality of Learning in Schools - Taty Fauzi; Mediarita Agustina; Syafwatul Putria H; Rytha Petrossky (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This research is a library study aimed at analyzing the various reasons for curriculum changes in Indonesia. Curriculum evaluation plays a crucial role in ensuring the quality and relevance of education by adapting to the dynamic changes in society. It helps identify the strengths and weaknesses of the curriculum and provides recommendations for improvement. However, several problems arise during implementation, particularly when teachers feel the time allocated to adapt to the new curriculum is insufficient, coupled with gaps in school facilities that make the implementation appear forced. The evaluation focuses on several key aspects: content, learning strategies, media, student learning outcomes, and teacher readiness, as teachers are the main drivers of knowledge transfer in the classroom. The qualitative descriptive approach, in the form of library research, collects data through systematic reviews, analysis stages, and information extraction from various sources. Over the course of the education system in Indonesia, from 1947 to 2024, the curriculum has undergone numerous changes. While these changes aim to improve the learning process and achieve optimal educational quality, they have had both positive and negative impacts. The influence of political agendas and the priorities of the ruling government have significantly shaped these curriculum changes. Despite these challenges, the rationale behind the changes lies in the effort to improve the learning experience and keep educational content up to date, reflecting the needs of the times. In conclusion, curriculum changes are essential to maintaining educational relevance, but proper preparation, sufficient time for adaptation, and adequate facilities are critical to the successful implementation of these changes. The research highlights the ongoing struggle to balance educational reforms with practical considerations for educators and students alike.